Prevalence and impact of self‐reported irritable bowel symptoms in the general population. Issue 2 (1st March 2019) - Van den Houte, K; Carbone, F; Pannemans, J; Corsetti, M; Fischler, B; Piessevaux, H; Tack, J
Abstract : Background and aims: The symptom‐based diagnostic criteria for irritable bowel syndrome (IBS) have recently been revised in the Rome IV consensus. On the other hand, with rising public awareness of IBS, self‐diagnosis and self‐management is also increasing. We compared the prevalence and impact of Rome IV‐based IBS vs self‐diagnosed IBS in the general population. Methods: An internet panel filled out an online survey on bowel symptoms and their impact on health care utilization and daily activities. Results: A representative internet panel of 1012 individuals completed the online survey. Bowel symptoms were present in 68.6% of the population. Of these, 21% consulted a physician for these symptoms in the last year and 42% earlier. Rome IV IBS criteria were fulfilled by 5.5%, and these were younger and more likely to be female. In this subset, 37% had consulted a physician for IBS symptoms in the preceding year and 29% had done so earlier. A colonoscopy had been performed in 22%. Based on a brief description, 17.6% of the population self‐identified as suffering from IBS ( p < 0.001 compared to Rome IV IBS prevalence), and these were more likely to be female. Concordance with the Rome IV criteria was only 25%, but except for a lower reporting of pain, the symptom pattern, severity, impact on daily life, inability to work and health care utilization were similar to the Rome IV group. A total of 134 days of absence from work were attributed to bowel symptoms in those self‐reporting with IBS. Conclusion: In the general population, bowel symptoms are highly prevalent, and the self‐reported "IBS" is three times more prevalent than according to Rome IV criteria. Self‐reported IBS is associated with a similar impact on health care utilization and quality of life but a higher impact on absence from work.